Loud Snoring is A Risk Factor for Occupational Injury in Farmers - James A Dosman; Louise Hagel; Robert Skomro; Xiaoqun Sun; Andrew G Day; William Pickett (Canadian Respiratory Journal)
BACKGROUND: Loud snoring is a common symptom in the general population. The evidence-based literature indicates that snoring may be associated with sleep fragmentation and sleep apnea, which may affect cognitive function and predispose to occupational injury. High rates of occupational injury occur on farms and may be related to personal and health factors. Thus, loud snoring may not be a trivial symptom and should be considered as important in medical assessments.